Composite coating with long-acting antifogging function as well as preparation method and application of composite coating
By combining the photothermal and hygroscopic layer of cesium tungsten bronze nanoparticles in the coating, the problem that existing anti-fog technology is difficult to take into account transparency and anti-fog effect, and long-term anti-fog and high transparency driven by sunlight are achieved.
Patent Information
- Application Number
- CN202311310866.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-10-10
AI Technical Summary
The existing anti-fog technology has the problem of difficulty in taking into account both transparency and anti-fog effect, especially the single hygroscopic coating has a short anti-fog age and the single light-thermal coating has an anti-fog hysteresis.
A composite coating consisting of a photothermal layer composed of cesium tungsten bronze nanoparticles and a hygroscopic layer with hygroscopic function is used to convert solar energy into thermal energy, and the hygroscopic layer absorbs condensed droplets to achieve long-term anti-fog.
It achieves long-term anti-fog driven by solar light, maintains high transparency, and maintains frost resistance in low temperature environments. It is suitable for car windshields, aircraft windows and other scenarios.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of coating materials, and specifically comprises a composite coating with long-lasting anti-fogging properties, a preparation method and an application thereof. Background Art
[0002] Fog can cause image distortion, seriously affect the normal use of transparent equipment, and even pose a potential risk to our health and safety. Therefore, it is critical to develop effective anti-fog technology. The current anti-fog technology is divided into active and passive categories according to whether external energy input is required. Passive anti-fog is based on surface wettability to construct super-hydrophobic, super-hydrophilic or hygroscopic surfaces. Although it consumes zero energy, the super-hydrophobic surface is only effective for large water droplets in the micron range, and the structural design is complex. Super-hydrophilic surfaces are easily contaminated by the outside world and have a short lifespan. Hygroscopic coatings rely on hydrogen bonding interactions between or within polymer molecules rich in polar groups to achieve anti-fog effects, but because of their limited water absorption capacity, if the inhaled droplets cannot evaporate in time, it will not only affect the anti-fog performance of the coating, but may also frost and ice in low temperature environments, and cannot be long-lasting and durable.
[0003] Active anti-fog is based on the principles of thermodynamics, using external input energy to heat the surface, which can fundamentally solve the fogging problem. However, this method requires additional equipment and consumes energy such as electricity, which is contrary to the requirements of energy conservation and environmental protection. Recently, a promising new strategy is to use photothermal materials to convert solar energy into thermal energy, which is expected to be applied in the field of anti-fog coatings. However, most photothermal materials show full-spectrum absorption of sunlight, which contradicts the high transparency required for anti-fog. In addition, since it takes a certain amount of time for the photothermal surface to heat up under light, it cannot resist the condensation of fog in time at the beginning of light. It can be seen that both active and passive anti-fog technologies have certain defects. Therefore, it is urgent to develop a new type of long-lasting anti-fog technology. Summary of the invention
[0004] In view of the above problems existing in the prior art, the first object of the present invention is to provide a composite coating with long-term anti-fogging. The composite coating has both high transparency and good photothermal performance, and can achieve long-term anti-fogging under the drive of sunlight, which can solve the problem of short anti-fogging time of a single hygroscopic coating and the problem of delayed anti-fogging of a single photothermal coating.
[0005] The second object of the present invention is to provide a method for preparing the composite coating as described above.
[0006] The third object of the present invention is to provide an application of the composite coating as described above in the anti-fog field.
[0007] To achieve the above first object, the technical solution adopted by the present invention includes:
[0008] The present invention discloses a composite coating with long-term anti-fogging, wherein the composite coating comprises a photothermal layer with photothermal conversion performance and a hygroscopic layer with hygroscopic function, which are arranged in sequence;
[0009] The photothermal layer includes cesium tungsten bronze nanoparticles.
[0010] The composite coating provided by the present invention is used to solve the problem of short anti-fog timeliness of a single hygroscopic coating and the problem of delayed anti-fog of a single photothermal coating. It effectively combines active and passive anti-fog modes. Once fogging begins, the hygroscopic layer located on the outside can be used to absorb condensed fog droplets, achieving an initial anti-fog effect when there is no sunlight or just exposed to sunlight. Thereafter, as the cesium tungsten bronze nanoparticles continuously and rapidly convert the incident solar energy into thermal energy, the condensed fog droplets evaporate, achieving a long-term anti-fog effect driven by sunlight. Therefore, the composite coating provided by the present invention has broad application prospects in scenes such as automobile windshields, aircraft windows, goggles, and building glass.
[0011] In the technical solution of the present invention, it is particularly critical to screen suitable photothermal materials. Not only should we pay attention to the photothermal conversion efficiency of the photothermal material, which is the key to directly affecting the evaporation rate of droplets, but we should also pay attention to the absorption spectrum of the photothermal material. If the absorption spectrum is not suitable (for example, full spectrum absorption), the transmittance of the composite coating cannot be effectively guaranteed, and it will be difficult to meet the application requirements. Finally, through a large number of experimental screenings, it was determined that the photothermal material that is compatible with the material used in the hygroscopic layer of the present invention is cesium tungsten bronze nanoparticles. This compatibility means that the heat energy converted by the photothermal material is sufficient to gradually establish a dynamic balance between the condensation and evaporation of the droplets, so that fog will not be generated during the whole process, and the composite coating can maintain a high transmittance.
[0012] Furthermore, the cesium tungsten bronze nanoparticles are hexagonal crystals with a size of 10-100 nm.
[0013] Furthermore, the thickness of the photothermal layer in the composite coating is 200-600 nm, and the thickness of the hygroscopic layer is 20-150 μm;
[0014] The average light transmittance of the composite coating in the range of 400-720nm is ≥60%, and the maximum light transmittance is above 75%;
[0015] The water contact angle of the composite coating decreases from 50-70° to 20-40° within 800 seconds.
[0016] To achieve the above second purpose, the technical solution adopted by the present invention includes:
[0017] The present invention discloses a method for preparing the composite coating as described above, comprising the following steps:
[0018] 1) Preparation of photothermal layer slurry:
[0019] Cesium tungsten bronze nanoparticles are added into a solvent under stirring, and a nanopowder dispersion is obtained by ultrasonic dispersion;
[0020] A water-based coating emulsion is mixed with deionized water to obtain a film-forming agent;
[0021] Mixing the film-forming agent with the nano-powder dispersion to obtain a photothermal layer slurry;
[0022] 2) Preparation of moisture absorbing layer slurry:
[0023] The first component and the second component are mixed evenly, stirred, ultrasonically or statically degassed to obtain a moisture absorbing layer slurry;
[0024] Wherein, the first component is selected from an aqueous solution of a polymer containing hydroxyl groups in the main chain or side chain or an aqueous solution of a polymer containing amino groups in the main chain or side chain;
[0025] The second component is selected from an inorganic metal ion compound solution or an aqueous solution of a polymer having a carboxyl group in the main chain or side chain;
[0026] 3) Preparation of photothermal layer:
[0027] Coating the photothermal layer slurry obtained in step 1) on the cleaned substrate, and drying to obtain a photothermal layer;
[0028] 4) Preparation of composite coating:
[0029] The hygroscopic layer slurry obtained in step 2) is coated again on the photothermal layer obtained in step 3) and dried to obtain the result.
[0030] Further, in step 1), the cesium tungsten bronze nanoparticles in the nano-powder dispersion account for 15-25wt%; illustratively, the cesium tungsten bronze nanoparticles in the nano-powder dispersion may account for 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, etc.;
[0031] The cesium tungsten bronze nanoparticles in the photothermal layer slurry account for 5-20wt%; illustratively, the cesium tungsten bronze nanoparticles in the photothermal layer slurry may account for 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt% and the like.
[0032] Furthermore, in step 1), the water-based coating emulsion includes but is not limited to one of a water-based acrylic emulsion, a silicone acrylic emulsion and a styrene acrylic emulsion.
[0033] Furthermore, in the film-forming agent, the mass ratio of the aqueous coating emulsion to deionized water is 1:0-5; illustratively, the film-forming agent may not contain deionized water, and when containing deionized water, the mass ratio of the aqueous coating emulsion to deionized water may be 1:1, 1:2, 1:3, 1:4, 1:5, etc.
[0034] Further, the polymer contained in the first component includes, but is not limited to, one or more of polyvinyl alcohol, polyethylene glycol, block copolymers of polyethylene glycol, polyvinyl amine and polyacrylamine;
[0035] Inorganic metal ion compounds include, but are not limited to, compounds such as copper chloride, zinc chloride, and iron chloride that can form coordination bonds with lone pairs of electrons on hydroxyl oxygen;
[0036] The polymer contained in the second component includes, but is not limited to, one or more of polyacrylic acid, polymethacrylic acid, polybutenoic acid and polyvalenoic acid.
[0037] Further, when the hygroscopic layer slurry is composed of a polymer in a first component and an inorganic metal ion compound solution, the molar ratio of the polymer to the inorganic metal ion compound in the first component is 10-50:1; illustratively, the molar ratio of the polymer to the inorganic metal ion compound in the first component can be 10:1, 20:1, 30:1, 40:1, 50:1, and the like.
[0038] Further, when the hygroscopic layer slurry is composed of a polymer in a first component and a polymer in a second component, the molar ratio of the polymer contained in the first component to the polymer contained in the second component is 1-50:1; illustratively, the molar ratio of the polymer contained in the first component to the polymer contained in the second component can be 1:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1 and the like.
[0039] Furthermore, the substrate is selected from acrylic glass, automobile glass, window glass or equipment glass. When cleaning the substrate, the following steps can be adopted:
[0040] The substrate was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 5-20 min respectively, and then cleaned with oxygen plasma after drying;
[0041] The oxygen plasma cleaning time is 5-10 min, the voltage is 600-800 V, and the oxygen flow rate is 800-1000 mL / min.
[0042] Furthermore, the coating methods used in step 3) and step 4) are conventional coating methods used in the art, including but not limited to spin coating, spray coating, pulling, scraping, roller coating or manual coating.
[0043] Furthermore, in step 3), the drying temperature of the photothermal layer is 20-40° C., and the drying time is 10-30 min.
[0044] Furthermore, in step 4), the drying temperature of the hygroscopic layer is 40-80° C., and the drying time is 2-8 hours.
[0045] Furthermore, the cesium tungsten bronze nanoparticles are prepared by a classical solvothermal method, the steps of which are as follows:
[0046] The tungsten-containing compound is dissolved in anhydrous ethanol, and then the cesium-containing compound is added to obtain a mixed solution;
[0047] Acetic acid is added dropwise into the mixed solution, and cesium tungsten bronze nanoparticles are prepared by a solvothermal method.
[0048] Of course, those skilled in the art can also choose other preparation methods to prepare cesium tungsten bronze nanoparticles, such as hydrothermal method, chemical vapor deposition method, solid phase method, etc., all of which can obtain similar anti-fog effects. Therefore, the specific preparation method of cesium tungsten bronze nanoparticles is not limited.
[0049] Furthermore, the tungsten-containing compound includes but is not limited to one or more of tungsten chloride, sodium tungstate and tungstic acid; the cesium-containing compound includes but is not limited to one or more of cesium hydroxide monohydrate, cesium carbonate and cesium sulfate.
[0050] Furthermore, the concentration of the tungsten-containing compound in the mixed solution is 0.7-1wt%; illustratively, the concentration of the tungsten-containing compound in the mixed solution may be 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, and the like.
[0051] Furthermore, the concentration of the cesium-containing compound in the mixed solution is 0.1-0.3 wt %; illustratively, the concentration of the cesium-containing compound in the mixed solution may be 0.1 wt %, 0.2 wt %, 0.3 wt %, and the like.
[0052] Further, the volume ratio of the anhydrous ethanol to the acetic acid is 8:1.5-3; illustratively, the volume ratio of the anhydrous ethanol to the acetic acid may be 8:1.5, 8:2, 8:2.5, 8:3, and the like.
[0053] Furthermore, the reaction temperature in the solvent thermal method is 200-240° C., and the reaction time is 18-24 hours.
[0054] To achieve the third objective, the technical solution adopted by the present invention includes:
[0055] The present invention discloses a film-coated glass, which is obtained by coating the composite coating as mentioned above on a glass substrate.
[0056] Furthermore, the glass substrate includes but is not limited to acrylic glass, automobile glass, window glass or equipment glass.
[0057] Beneficial effects of the present invention:
[0058] The present invention provides a composite coating with long-term anti-fog effect, and a preparation method and application thereof. The composite coating effectively combines active and passive anti-fog modes. The outer adsorption layer can absorb condensed fog droplets to achieve the purpose of initial anti-fog. At the same time, the inner photothermal layer quickly converts the incident solar energy into thermal energy, causing the condensed fog droplets to gradually evaporate, and finally achieves a long-term anti-fog effect. The composite coating specifically includes the following advantages:
[0059] 1. The composite coating has good visible light transmittance, with an average transmittance of ≥60% in the range of 400-720nm wavelength and a maximum transmittance of more than 75%.
[0060] 2. The composite coating has good light-to-heat conversion performance, and the internal surface temperature can reach above 57°C in 600 seconds under one sun intensity.
[0061] 3. The composite coating has good anti-frost performance. It will not frost after being taken out from a -20℃ refrigerator for 24 hours.
[0062] 4. The composite coating can maintain a clear view for at least 6 hours when placed 5 cm above 65°C hot water under sunlight simulated by a xenon lamp.
[0063] 5. The composite coating has good mechanical properties. The surface of the composite coating was rubbed repeatedly 5000 times with a fiber cloth at a pressure of 55 kPa, and the light transmittance of the composite coating did not change significantly.
[0064] 6. The composite coating has good light-heat cycle stability. The composite coating was subjected to 50 heating and cooling cycles. During these 50 heating and cooling cycles, all temperature curves were similar and no significant changes occurred. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.
[0066] Figure 1 The powder XRD spectrum and transmission electron microscope image of the cesium tungsten bronze nanoparticles prepared in Example 1 are shown; wherein, Figure 1 a is the powder XRD spectrum, and b is the transmission electron microscopy image.
[0067] Figure 2 The scanning electron microscope image and AFM image of the surface and cross section of the photothermal layer prepared in Example 2 are shown; wherein, Figure 2 a is a scanning electron microscope image, and b is an AFM image.
[0068] Figure 3 The scanning electron microscope image and AFM image of the surface of the composite coating prepared in Example 3 are shown; wherein, Figure 3 a is a scanning electron microscope image, and b is an AFM image.
[0069] Figure 4 The light transmittance curve of the composite coating prepared in Example 3 is shown.
[0070] Figure 5 The change of the water contact angle of the composite coating prepared in Example 3 over time is shown.
[0071] Figure 6 The temperature variation curve of the composite coating prepared in Example 3 under a xenon lamp and the anti-fog test photos of the coatings of Comparative Example 4 and Example 3 are shown; wherein, Figure 6 In the figure, a is a temperature change curve, and b is a photo of the anti-fog comparison test of the hygroscopic layer of comparative example 4 and the composite coating of embodiment 3.
[0072] Figure 7 The anti-fog test photos of the coating prepared in Comparative Example 5 and the anti-frost test photos of the coating prepared in Example 3 and Comparative Example 5 are shown, wherein: Figure 7 In the figure a is a photo of the anti-fog test of the coating prepared in Comparative Example 5 at different times, and in the figure b is a photo of the anti-frost test of the blank glass substrate, the coating prepared in Comparative Example 5, and the composite coating prepared in Example 3.
[0073] Figure 8 The transmittance spectrum of the composite coating prepared in Example 3 before and after the wear resistance test and the temperature change curve during 50 heating and cooling cycles are shown; wherein, Figure 8 In the figure, a is the transmittance spectrum, and b is the temperature change curve during 50 heating and cooling cycles.
[0074] Fig. 9 The following is a photograph of the outdoor anti-fog test of the composite coating prepared in Example 3. DETAILED DESCRIPTION
[0075] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and drawings. It should be clear that the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0076] In addition, unless otherwise specified, the raw materials used in the present invention can be obtained commercially, and any range recorded in the present invention includes the end value and any numerical value between the end values and any sub-range formed by the end value or any numerical value between the end values.
[0077] Example 1 Preparation of photothermal nanomaterial powder and photothermal layer slurry
[0078] 0.6 g of tungsten chloride was dissolved in 80 ml of anhydrous ethanol and stirred at room temperature for 15 min; then 0.13 g of cesium hydroxide monohydrate was added and stirred at room temperature for 10 min to obtain a mixed solution; 20 ml of acetic acid was added dropwise to the mixed solution and stirred for 15 min, then transferred to a reactor with a polytetrafluoroethylene liner and subjected to solvent thermal reaction at 220°C for 20 h; after the reaction, the solid sample was separated by centrifugation and washed with anhydrous ethanol and deionized water for at least three times, dried in a vacuum oven at 60°C overnight, and ground to obtain cesium tungsten bronze nanoparticle powder;
[0079] Under vigorous stirring, 12 parts by mass of nanoparticle powder were added to 60 parts by mass of deionized water, and ultrasonically dispersed for 10 minutes to obtain a uniform nanopowder dispersion; 8 parts by mass of aqueous acrylic emulsion was mixed with 10 parts by mass of deionized water to obtain a film-forming agent, which was then mixed and stirred with 50 parts by mass of the above nanopowder dispersion, and ultrasonically dispersed for 15 minutes to obtain a photothermal layer slurry with a cesium tungsten bronze nanoparticle content of 12wt%.
[0080] The X-ray diffraction peaks of the cesium tungsten bronze nanoparticle powder obtained by the solvothermal method correspond to the diffraction peaks of the standard hexagonal cesium tungsten bronze (e.g. Figure 1 As shown in a), it is a rod-like structure with a diameter of about 10nm and a length of 40-60nm (as shown in Figure 1 (as shown in b).
[0081] Example 2 Preparation of photothermal layer
[0082] The photothermal layer slurry obtained in Example 1 was applied on a cleaned glass substrate by spin coating and dried at room temperature for 10 minutes to obtain a photothermal layer with near-infrared shielding performance.
[0083] The obtained photothermal layer was subjected to scanning electron microscopy to observe its surface morphology and cross-section. The detailed results of the test are as follows: Figure 2 As shown in a, the thickness of the photothermal layer is about 400nm. Due to the presence of nanoparticles, its surface is very rough. The surface roughness of the photothermal layer is further characterized by AFM, as shown in Figure 2 As shown in b, the root mean square roughness of the photothermal layer surface is 22.3 nm.
[0084] Example 3 Preparation of photothermal / hygroscopic composite coating
[0085] (1) Preparation of moisture absorbing layer slurry:
[0086] 8 parts by mass of PVA were weighed and dissolved in 92 parts by mass of deionized water, and stirred in a water bath at 85° C. for 1 hour to obtain an 8wt% PVA aqueous solution; 2.05 parts by mass of zinc chloride were dissolved in 30 parts by mass of 3M dilute hydrochloric acid, and stirred evenly to obtain a zinc chloride solution, and 2.4 parts by mass of the zinc chloride solution were added dropwise to 20 parts by mass of the 8wt% PVA aqueous solution, and stirred at room temperature until fully mixed to obtain a moisture absorption layer slurry;
[0087] (2) The hygroscopic layer slurry prepared in step (1) is coated on the photothermal layer obtained in Example 2 by a blade coating method, and is placed in an oven at 60° C. and dried for 4 h to obtain a photothermal / hygroscopic composite coating; wherein the thickness of the hygroscopic layer is controlled to be 20 μm by the program setting of the coating machine.
[0088] The obtained photothermal / hygroscopic composite coating was subjected to scanning electron microscopy to observe its surface morphology. The detailed results of the test are as follows: Figure 3 As shown in a, the surface of the composite coating after coating the hygroscopic layer is very smooth; the surface roughness of the photothermal / hygroscopic composite coating is further characterized by AFM, as shown in Figure 3 As shown in b, the root mean square roughness of the surface of the photothermal / hygroscopic composite coating is 0.44 nm.
[0089] The light transmittance of the photothermal / hygroscopic composite coating was tested by Figure 4 It can be seen that the maximum transmittance of the photothermal / hygroscopic composite coating in the range of light wavelength of 400-720nm is 80.92%, the average transmittance is 76.38%, and the transmittance in the near-infrared region is as low as 20.60%.
[0090] The water contact angle of the photothermal / hygroscopic composite coating was tested by dropping a 5 μl water droplet on the composite coating surface and taking photos of the water contact angle at regular intervals. For the objectivity of the data, three different points were taken for each sample for testing. Figure 5 As shown, the water contact angle of the photothermal / hygroscopic composite coating gradually decreases with time, from 67.13° to 31.33° within 800 seconds, while the water contact angle of the control blank glass remains basically unchanged, indicating that the surface of the composite coating has good hygroscopicity.
[0091] The surface temperature of the photothermal / hygroscopic composite coating and the control blank glass was measured under one sun intensity. Figure 6 As shown in a, the photothermal / hygroscopic composite coating has good photothermal conversion performance, and the surface temperature can reach at least 64°C within 600s.
[0092] The photothermal / hygroscopic composite coating was exposed to sunlight simulated by a xenon lamp with a light intensity of 1000W m -2 The coated side was placed 5 cm above 65°C hot water. Figure 6 As shown in b, the photothermal / hygroscopic composite coating has a long-lasting anti-fog function and maintains a clear field of vision at the 6th hour of the test; the glass sheet coated with the photothermal / hygroscopic composite coating is placed in a refrigerator at -20°C for 24 hours for anti-frost test. Figure 7 As shown in b, the surface of the photothermal / hygroscopic composite coating remains transparent and has anti-frost function.
[0093] The wear resistance of the photothermal / hygroscopic composite coating was tested. The photothermal / hygroscopic composite coating was repeatedly rubbed 5000 times with a fiber cloth at a pressure of 55 kPa, and the changes in the light transmittance of the coating before and after the friction were compared. Figure 8 As shown in a, after friction, the maximum transmittance of the photothermal / hygroscopic composite coating in the range of 400-720nm is 80.85%, and the average transmittance is 76.15%, which is almost unchanged compared with before friction.
[0094] In order to evaluate the effects of repeated and long-term illumination on the photothermal conversion performance of the photothermal / hygroscopic composite coating, the sample was repeatedly heated and cooled for 50 cycles under one sun intensity. Figure 8 As shown in middle b, all the cycle curves of the photothermal / hygroscopic composite coating during repeated heating (xenon lamp on) and cooling (xenon lamp off) are similar without significant changes, showing good photothermal stability.
[0095] The feasibility of the anti-fog performance of the photothermal / hygroscopic composite coating was tested. A glass sheet coated with the composite coating was placed 5 cm above 65°C hot water in the sun. The anti-fog test results are as follows: Fig. 9 The photothermal / hygroscopic composite coating maintained a clear view throughout the experiment, but the control sample coated with only the hygroscopic layer was severely fogged.
[0096] Example 4 Preparation of photothermal / hygroscopic composite coating
[0097] (1) Preparation of photothermal layer slurry:
[0098] 0.6 g of tungsten chloride was dissolved in 80 ml of anhydrous ethanol and stirred at room temperature for 15 min; then 0.13 g of cesium hydroxide monohydrate was added and stirred at room temperature for 10 min to obtain a mixed solution; 20 ml of acetic acid was added dropwise to the mixed solution and stirred for 15 min, then transferred to a reactor with a polytetrafluoroethylene liner and subjected to solvent thermal reaction at 220°C for 20 h; after the reaction, the solid sample was separated by centrifugation and washed with anhydrous ethanol and deionized water for at least three times, dried in a vacuum oven at 60°C overnight, and ground to obtain cesium tungsten bronze nanoparticle powder;
[0099] Under vigorous stirring, 12 parts by mass of nanoparticle powder were added to 60 parts by mass of deionized water, and ultrasonically dispersed for 15 minutes to obtain a uniform nanopowder dispersion; 8 parts by mass of aqueous acrylic emulsion were mixed with 18 parts by mass of deionized water to obtain a film-forming agent, which was then mixed and stirred with 24 parts by mass of the above nanopowder dispersion, and ultrasonically dispersed for 15 minutes to obtain a photothermal layer slurry with a cesium tungsten bronze nanoparticle content of 8wt%.
[0100] (2) Preparation of moisture absorbing layer slurry:
[0101] Weigh 8 parts by mass of PVA and dissolve it in 92 parts by mass of deionized water, stir it in a water bath at 85°C for 1 hour to obtain an 8wt% PVA aqueous solution; dissolve 2.05 parts by mass of zinc chloride in 30 parts by mass of 3M dilute hydrochloric acid to obtain a zinc chloride solution, stir it evenly, take 2.4 parts by mass of the zinc chloride solution and add it dropwise to 20 parts by mass of the 8wt% PVA aqueous solution, stir it at room temperature until it is fully mixed, and obtain a hygroscopic layer slurry.
[0102] (3) The photothermal layer slurry obtained in step (1) is applied onto a clean glass substrate by spin coating, and dried at room temperature for 10 minutes to obtain a photothermal layer with near-infrared shielding performance.
[0103] The hygroscopic layer slurry prepared in step (2) is coated on the photothermal layer obtained in step (3) by a doctor blade coating method, and is placed in a 60° C. oven and dried for 4 hours to obtain a photothermal / hygroscopic composite coating.
[0104] The light transmittance, light-to-heat conversion performance and anti-fogging performance of the photothermal / hygroscopic composite coating obtained in Example 4 were measured. The results are shown in Table 1.
[0105] Example 5 Preparation of photothermal / hygroscopic composite coating
[0106] (1) Preparation of photothermal layer slurry:
[0107] 0.6 g of tungsten chloride was dissolved in 80 ml of anhydrous ethanol and stirred at room temperature for 15 min; then 0.13 g of cesium hydroxide monohydrate was added and stirred at room temperature for 10 min to obtain a mixed solution; 20 ml of acetic acid was added dropwise to the mixed solution and stirred for 15 min, then transferred to a reactor with a polytetrafluoroethylene liner and subjected to solvent thermal reaction at 220°C for 20 h; after the reaction, the solid sample was separated by centrifugation and washed with anhydrous ethanol and deionized water for at least three times, dried in a vacuum oven at 60°C overnight, and ground to obtain cesium tungsten bronze nanoparticle powder;
[0108] Under vigorous stirring, 12 parts by mass of nanoparticle powder were added to 60 parts by mass of deionized water, and ultrasonically dispersed for 15 minutes to obtain a uniform nanopowder dispersion; 5 parts by mass of aqueous acrylic emulsion were taken, mixed and stirred with 50 parts of the above nanopowder dispersion, and ultrasonically dispersed for 15 minutes to obtain a photothermal layer slurry with a cesium tungsten bronze nanoparticle content of 15wt%.
[0109] (2) Preparation of moisture absorbing layer slurry:
[0110] Weigh 8 parts by mass of PVA and dissolve it in 92 parts by mass of deionized water, stir it in a water bath at 85°C for 1 hour to obtain an 8wt% PVA aqueous solution; dissolve 2.05 parts by mass of zinc chloride in 30 parts by mass of 3M dilute hydrochloric acid to obtain a zinc chloride solution, stir it evenly, take 2.4 parts by mass of the zinc chloride solution and add it dropwise to 20 parts by mass of the 8wt% PVA aqueous solution, stir it at room temperature until it is fully mixed, and obtain a hygroscopic layer slurry.
[0111] (3) The photothermal layer slurry obtained in step (1) is applied onto a clean glass substrate by spin coating, and dried at room temperature for 10 minutes to obtain a photothermal layer with near-infrared shielding performance.
[0112] The hygroscopic layer slurry prepared in step (2) is coated on the photothermal layer obtained in step (3) by a doctor blade coating method, and is placed in a 60° C. oven and dried for 4 hours to obtain a photothermal / hygroscopic composite coating.
[0113] The light transmittance, light-to-heat conversion performance and anti-fogging performance of the photothermal / hygroscopic composite coating obtained in Example 5 were measured. The results are shown in Table 1.
[0114] Example 6 Preparation of photothermal / hygroscopic composite coating
[0115] The preparation method is basically the same as that of Example 3, except that the zinc chloride solution in step (1) is replaced by a copper chloride solution of the same concentration.
[0116] The light transmittance, light-to-heat conversion performance and anti-fogging performance of the photothermal / hygroscopic composite coating obtained in Example 6 were measured. The results are shown in Table 1.
[0117] Example 7 Preparation of photothermal / hygroscopic composite coating
[0118] The preparation method is basically the same as that of Example 3, except that the zinc chloride solution in step (1) is replaced by a polyacrylic acid aqueous solution. The specific implementation method is:
[0119] (1) Preparation of photothermal nanomaterial powder and photothermal layer slurry:
[0120] 0.6 g of tungsten chloride was dissolved in 80 ml of anhydrous ethanol and stirred at room temperature for 15 min; then 0.13 g of cesium hydroxide monohydrate was added and stirred at room temperature for 10 min to obtain a mixed solution; 20 ml of acetic acid was added dropwise to the mixed solution and stirred for 15 min, then transferred to a reactor with a polytetrafluoroethylene liner and subjected to solvent thermal reaction at 220°C for 20 h; after the reaction, the solid sample was separated by centrifugation and washed with anhydrous ethanol and deionized water for at least three times, dried in a vacuum oven at 60°C overnight, and ground to obtain cesium tungsten bronze nanoparticle powder;
[0121] Under vigorous stirring, 12 parts by mass of nanoparticle powder were added to 60 parts by mass of deionized water, and ultrasonically dispersed for 10 minutes to obtain a uniform nanopowder dispersion; 8 parts by mass of aqueous acrylic emulsion was mixed with 10 parts by mass of deionized water to obtain a film-forming agent, which was then mixed and stirred with 50 parts by mass of the above nanopowder dispersion, and ultrasonically dispersed for 15 minutes to obtain a photothermal layer slurry with a cesium tungsten bronze nanoparticle content of 12wt%.
[0122] (2) Preparation of moisture absorbing layer slurry:
[0123] Weigh 8 parts of PVA and dissolve them in 92 parts of deionized water, stir in a water bath at 85°C for 1 hour to obtain an 8wt% PVA aqueous solution; prepare a 53wt% polyacrylic acid aqueous solution, take 5ml and add it dropwise to 45ml of the 8wt% PVA aqueous solution, and stir at room temperature until fully mixed; adjust the pH of the obtained mixed solution to 4 with hydrochloric acid, stir, and degas by ultrasonication or standing to obtain a hygroscopic layer slurry.
[0124] (3) The photothermal layer slurry obtained in step (1) is applied onto a clean glass substrate by spin coating, and dried at room temperature for 10 minutes to obtain a photothermal layer with near-infrared shielding performance.
[0125] The hygroscopic layer slurry prepared in step (2) is coated on the photothermal layer obtained in step (3) by a doctor blade coating method, and is placed in a 60° C. oven and dried for 6 hours to obtain a photothermal / hygroscopic composite coating.
[0126] The light transmittance, light-to-heat conversion performance and anti-fogging performance of the photothermal / hygroscopic composite coating obtained in Example 7 were measured. The results are shown in Table 1.
[0127] Example 8 Preparation of photothermal / hygroscopic composite coating
[0128] The preparation method is basically the same as that of Example 7, except that the polyacrylic acid aqueous solution in step (2) is replaced by a polymethacrylic acid aqueous solution of the same concentration.
[0129] The light transmittance, light-to-heat conversion performance and anti-fogging performance of the photothermal / hygroscopic composite coating obtained in Example 8 were measured. The results are shown in Table 1.
[0130] Example 9 Preparation of photothermal / hygroscopic composite coating
[0131] The preparation method is basically the same as that of Example 7, except that the PVA aqueous solution in step (2) is replaced by a polyethylene glycol aqueous solution of the same concentration.
[0132] The light transmittance, light-to-heat conversion performance and anti-fogging performance of the photothermal / hygroscopic composite coating obtained in Example 9 were measured. The results are shown in Table 1.
[0133] Example 10 Preparation of photothermal / hygroscopic composite coating
[0134] The preparation method is basically the same as that of Example 9, except that the polyethylene glycol aqueous solution in step (2) is replaced by a polyvinylamine aqueous solution.
[0135] The light transmittance, light-to-heat conversion performance and anti-fogging performance of the photothermal / hygroscopic composite coating obtained in Example 10 were measured. The results are shown in Table 1.
[0136] Comparative Example 1
[0137] The difference between Comparative Example 1 and Example 3 is that the preparation and mixing steps of the film-forming agent are missing in Comparative Example 1. The specific implementation method is:
[0138] (1) Preparation of photothermal layer slurry:
[0139] 0.6 g of tungsten chloride was dissolved in 80 ml of anhydrous ethanol and stirred at room temperature for 15 min; then 0.13 g of cesium hydroxide monohydrate was added and stirred at room temperature for 10 min to obtain a mixed solution; 20 ml of acetic acid was added dropwise to the mixed solution and stirred for 15 min, then transferred to a reactor with a polytetrafluoroethylene liner and subjected to solvent thermal reaction at 220°C for 20 h; after the reaction, the solid sample was separated by centrifugation and washed with anhydrous ethanol and deionized water for at least three times, dried in a vacuum oven at 60°C overnight, and ground to obtain cesium tungsten bronze nanoparticle powder;
[0140] Under vigorous stirring, 12 parts by mass of nanoparticle powder was added to 60 parts by mass of deionized water, and ultrasonically dispersed for 10 minutes to obtain a uniform nanopowder dispersion; 18 parts by mass of deionized water was taken, mixed with 50 parts by mass of the above nanopowder dispersion, and ultrasonically dispersed for 15 minutes to obtain a photothermal layer slurry.
[0141] (2) Preparation of moisture absorbing layer slurry:
[0142] Weigh 8 parts by mass of PVA and dissolve it in 92 parts by mass of deionized water, stir in a water bath at 85°C for 1 hour to obtain an 8wt% PVA aqueous solution; dissolve 2.05 parts by mass of zinc chloride in 30 parts by mass of 3M dilute hydrochloric acid to obtain a zinc chloride solution, take 2.4 parts by mass of the zinc chloride solution and add it dropwise to 20 parts by mass of the 8wt% PVA aqueous solution, stir at room temperature until fully mixed, and obtain a hygroscopic layer slurry.
[0143] (3) The nanopowder dispersion obtained in step (1) is applied onto a clean glass substrate by spin coating, and dried at room temperature for 10 minutes to obtain a photothermal layer.
[0144] The hygroscopic layer slurry prepared in step (2) is coated on the photothermal layer obtained in step (3) by a doctor blade coating method, and is placed in a 60° C. oven and dried for 4 hours to obtain a photothermal / hygroscopic composite coating.
[0145] The light transmittance, photothermal conversion performance and anti-fogging performance of the photothermal / hygroscopic composite coating obtained in Comparative Example 1 were measured, and the results are shown in Table 1. Since no film-forming agent was added, the nanopowder dispersion had low viscosity and poor film-forming property on the substrate, and the obtained coating had low absorption in the near-infrared region, poor photothermal conversion performance, and could not provide long-term anti-fogging.
[0146] Comparative Example 2
[0147] The difference between Comparative Example 2 and Example 3 is that the content of cesium tungsten bronze nanoparticles in the photothermal layer slurry is increased to 30wt% in Comparative Example 2. The specific implementation method is:
[0148] (1) Preparation of photothermal layer slurry:
[0149] 0.6 g of tungsten chloride was dissolved in 80 ml of anhydrous ethanol and stirred at room temperature for 15 min; then 0.13 g of cesium hydroxide monohydrate was added and stirred at room temperature for 10 min to obtain a mixed solution; 20 ml of acetic acid was added dropwise to the mixed solution and stirred for 15 min, then transferred to a reactor with a polytetrafluoroethylene liner and subjected to solvent thermal reaction at 220°C for 20 h; after the reaction, the solid sample was separated by centrifugation and washed with anhydrous ethanol and deionized water for at least three times, dried in a vacuum oven at 60°C overnight, and ground to obtain cesium tungsten bronze nanoparticle powder;
[0150] Under vigorous stirring, 5 parts by mass of nanoparticle powder are added to 5 parts by mass of deionized water, and ultrasonically dispersed for 10 minutes to obtain a uniform nanopowder dispersion; 26 parts by mass of aqueous acrylic emulsion are mixed with 54 parts by mass of deionized water to obtain a film-forming agent, which is then mixed and stirred with 120 parts by mass of the above nanopowder dispersion, and ultrasonically dispersed for 15 minutes to obtain a photothermal layer slurry with a cesium tungsten bronze nanoparticle content of 30wt%.
[0151] (2) Preparation of hygroscopic layer slurry: Weigh 8 parts by mass of PVA and dissolve it in 92 parts by mass of deionized water, stir it in a water bath at 85°C for 1 hour to obtain an 8 wt% PVA aqueous solution; dissolve 2.05 parts by mass of zinc chloride in 30 parts by mass of 3M dilute hydrochloric acid to obtain a zinc chloride solution, stir it evenly, take 2.4 parts by mass of the zinc chloride solution and add it dropwise to 20 parts by mass of the 8 wt% PVA aqueous solution, stir it at room temperature until it is fully mixed, and obtain a hygroscopic layer slurry.
[0152] (3) The nanopowder dispersion obtained in step (1) is applied onto a clean glass substrate by spin coating, and dried at room temperature for 10 minutes to obtain a photothermal layer.
[0153] The hygroscopic layer slurry prepared in step (2) is coated on the photothermal layer obtained in step (3) by a doctor blade coating method, and is placed in a 60° C. oven and dried for 4 hours to obtain a photothermal / hygroscopic composite coating.
[0154] The photothermal / hygroscopic composite coating obtained in Comparative Example 2 has a high content of nanoparticles. The coating has a large haze and poor transparency when observed with the naked eye, and no longer has the application value of anti-fogging on a transparent substrate.
[0155] Comparative Example 3
[0156] The difference between Comparative Example 3 and Example 3 is that the preparation and addition steps of the zinc chloride solution are missing in the preparation process of the moisture absorption layer slurry in Comparative Example 3. The specific implementation method is:
[0157] (1) Preparation of photothermal layer slurry:
[0158] 0.6 g of tungsten chloride was dissolved in 80 ml of anhydrous ethanol and stirred at room temperature for 15 min; then 0.13 g of cesium hydroxide monohydrate was added and stirred at room temperature for 10 min to obtain a mixed solution; 20 ml of acetic acid was added dropwise to the mixed solution and stirred for 15 min, then transferred to a reactor with a polytetrafluoroethylene liner and subjected to solvent thermal reaction at 220°C for 20 h; after the reaction, the solid sample was separated by centrifugation and washed with anhydrous ethanol and deionized water for at least three times, dried in a vacuum oven at 60°C overnight, and ground to obtain cesium tungsten bronze nanoparticle powder;
[0159] Under vigorous stirring, 12 parts by mass of nanoparticle powder were added to 60 parts by mass of deionized water, and ultrasonically dispersed for 10 minutes to obtain a uniform nanopowder dispersion; 8 parts by mass of aqueous acrylic emulsion was mixed with 10 parts by mass of deionized water to obtain a film-forming agent, which was then mixed and stirred with 50 parts by mass of the above nanopowder dispersion, and ultrasonically dispersed for 15 minutes to obtain a photothermal layer slurry.
[0160] (2) Preparation of moisture absorbing layer slurry:
[0161] 8 parts by weight of PVA were weighed and dissolved in 92 parts by weight of deionized water, and stirred in a water bath at 85° C. for 1 hour to obtain an 8 wt % PVA aqueous solution; the 8 wt % PVA aqueous solution was directly used as the slurry for the moisture absorption layer.
[0162] (3) The photothermal layer slurry obtained in step (1) is applied onto a clean glass substrate by spin coating, and dried at room temperature for 10 minutes to obtain a photothermal layer with near-infrared shielding performance.
[0163] The hygroscopic layer slurry prepared in step (2) is coated on the photothermal layer obtained in step (3) by a doctor blade coating method, and is placed in a 60° C. oven to dry for 4 hours to obtain a photothermal / hygroscopic composite coating.
[0164] Comparative Example 3 and Example 3 were immersed in deionized water at the same time. After 24 hours, it was found that Comparative Example 3 was severely wrinkled, while the appearance of Example 3 was not damaged at all, which proved that the zinc chloride added in Example 3 could enhance the adhesion and water resistance of the polymer.
[0165] Comparative Example 4
[0166] The difference between Comparative Example 4 and Example 3 is that the step of coating the photothermal layer is missing in Comparative Example 4. The specific implementation method is:
[0167] (1) Preparation of moisture absorbing layer slurry:
[0168] Weigh 8 parts by mass of PVA and dissolve it in 92 parts by mass of deionized water, stir it in a water bath at 85°C for 1 hour to obtain an 8wt% PVA aqueous solution; dissolve 2.05 parts by mass of zinc chloride in 30 parts by mass of 3M dilute hydrochloric acid to obtain a zinc chloride solution, stir it evenly, take 2.4 parts by mass of the zinc chloride solution and add it dropwise to 20 parts by mass of the 8wt% PVA aqueous solution, stir it at room temperature until it is fully mixed, and obtain a hygroscopic layer slurry.
[0169] The hygroscopic layer slurry prepared in step (1) is coated on a clean glass substrate by a doctor blade method, and then placed in an oven at 60° C. and dried for 4 h to obtain a coating having only a hygroscopic layer.
[0170] After removing the first photothermal layer with photothermal conversion performance, the prepared hygroscopic layer does not have photothermal conversion performance, and the surface temperature does not increase significantly under the sunlight simulated by the xenon lamp; the hygroscopic layer coating obtained in Comparative Example 4 was subjected to an anti-fog test, and the test process was referred to Example 3. The results are as follows: Figure 6 As shown in b. In the early stage of the anti-fog test, the hygroscopic layer has an anti-fog effect, but as the test time increases, the hygroscopic layer gradually reaches the water absorption saturation limit, condensation droplets appear on the surface of the hygroscopic layer, and eventually gather into a water film, which cannot prevent fogging for a long time.
[0171] Comparative Example 5
[0172] The difference between Comparative Example 5 and Example 3 is that the step of coating the hygroscopic layer is missing in Comparative Example 5. The specific implementation method is:
[0173] (1) Preparation of photothermal nanomaterial powder and photothermal layer slurry:
[0174] 0.6 g of tungsten chloride was dissolved in 80 ml of anhydrous ethanol and stirred at room temperature for 15 min; then 0.13 g of cesium hydroxide monohydrate was added and stirred at room temperature for 10 min to obtain a mixed solution; 20 ml of acetic acid was added dropwise to the mixed solution and stirred for 15 min, then transferred to a reactor with a polytetrafluoroethylene liner and subjected to solvent thermal reaction at 220°C for 20 h; after the reaction, the solid sample was separated by centrifugation and washed with anhydrous ethanol and deionized water for at least three times, dried in a vacuum oven at 60°C overnight, and ground to obtain cesium tungsten bronze nanoparticle powder;
[0175] Under vigorous stirring, 12 parts by mass of nanoparticle powder were added to 60 parts by mass of deionized water, and ultrasonically dispersed for 10 minutes to obtain a uniform nanopowder dispersion; 8 parts by mass of aqueous acrylic emulsion was mixed with 10 parts by mass of deionized water to obtain a film-forming agent, which was then mixed and stirred with 50 parts by mass of the above nanopowder dispersion, and ultrasonically dispersed for 15 minutes to obtain a photothermal layer slurry with a cesium tungsten bronze nanoparticle content of 12wt%.
[0176] (2) The photothermal layer slurry obtained in step (1) is applied onto a clean glass substrate by spin coating, and dried at room temperature for 10 minutes to obtain a photothermal layer with near-infrared shielding performance.
[0177] After removing the second hygroscopic layer, the prepared photothermal layer still has photothermal conversion performance, and the change of surface temperature under the sunlight simulated by the xenon lamp is basically consistent with the photothermal / hygroscopic composite coating obtained in Example 3; the photothermal layer obtained by Comparative Example 5 was subjected to an anti-fog test, and the test process was referred to Example 3. The results are as follows: Figure 7In the initial stage of the anti-fog test, the photothermal layer was not anti-fog, but because the surface temperature of the photothermal layer rose rapidly under the simulated sunlight, the condensed droplets evaporated completely within 5 minutes, and then no more fogging occurred; the photothermal layer obtained in Comparative Example 5 was placed in a refrigerator at -20°C for 24 hours for anti-frost test. Figure 7 As shown in b, the photothermal layer does not have anti-frost properties.
[0178] Table 1 Performance comparison data of the coatings obtained in Examples 3-10 and Comparative Examples 1, 4-5
[0179]
[0180] Note: Long-term anti-fog means that the sample coated with the coating is placed 5 cm above 65℃ hot water under one sun intensity and there is no fogging on the surface for at least 6 hours.
[0181] It can be seen from Table 1 that the composite coatings prepared in Examples 3-10 all have long-lasting anti-fog properties driven by sunlight, among which Example 3 has the best spectral selectivity, with an average transmittance of 76.38% in the visible light region and an average transmittance as low as 20.60% in the near-infrared region. After irradiation at one sunlight intensity for 600 seconds, the surface temperature is higher than 64°C, showing long-lasting anti-fog properties driven by sunlight.
[0182] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A composite coating with long-lasting anti-fog properties, characterized in that: The composite coating comprises a photothermal layer with photothermal conversion performance and a hygroscopic layer with hygroscopic function, which are arranged in sequence; The photothermal layer includes cesium tungsten bronze nanoparticles.
2. The composite coating according to claim 1, characterized in that: The cesium tungsten bronze nanoparticles are hexagonal crystals with a size of 10-100 nm.
3. The composite coating according to claim 1, characterized in that: The thickness of the photothermal layer in the composite coating is 200-600 nm, and the thickness of the hygroscopic layer is 20-150 μm; The average light transmittance of the composite coating in the range of 400-720nm is ≥60%; The water contact angle of the composite coating decreases from 50-70° to 20-40° within 800 seconds.
4. The method for preparing the composite coating according to any one of claims 1 to 3, characterized in that: The steps include: 1) Preparation of photothermal layer slurry: The cesium tungsten bronze nanoparticles are added into a solvent and dispersed by ultrasonic to obtain a nanopowder dispersion; A water-based coating emulsion is mixed with deionized water to obtain a film-forming agent; Mixing the film-forming agent with the nano-powder dispersion to obtain a photothermal layer slurry; 2) Preparation of moisture absorbing layer slurry: The first component and the second component are mixed evenly, stirred, ultrasonically or statically degassed to obtain a moisture absorbing layer slurry; Wherein, the first component is selected from an aqueous solution of a polymer containing hydroxyl groups in the main chain or side chain or an aqueous solution of a polymer containing amino groups in the main chain or side chain; The second component is selected from an inorganic metal ion compound solution or an aqueous solution of a polymer having a carboxyl group in the main chain or side chain; 3) Preparation of photothermal layer: Coating the photothermal layer slurry obtained in step 1) on the cleaned substrate, and drying to obtain a photothermal layer; 4) Preparation of composite coating: The hygroscopic layer slurry obtained in step 2) is coated again on the photothermal layer obtained in step 3), and after drying, a composite coating is obtained.
5. The preparation method according to claim 4, characterized in that: In step 1), the cesium tungsten bronze nanoparticles account for 15-25wt% in the nano-powder dispersion; and the cesium tungsten bronze nanoparticles account for 5-20wt% in the photothermal layer slurry.
6. The preparation method according to claim 4, characterized in that: In step 1), the aqueous coating emulsion is selected from one of aqueous acrylic emulsion, silicone acrylic emulsion and styrene acrylic emulsion; Preferably, in the film-forming agent, the mass ratio of the aqueous coating emulsion to deionized water is 1:0-5.
7. The preparation method according to claim 4, characterized in that: The polymer contained in the first component is selected from one or more of polyvinyl alcohol, polyethylene glycol, block copolymers of polyethylene glycol, polyvinyl amine and polyacrylamine; The inorganic metal ion compound is selected from one or more of cupric chloride, zinc chloride and ferric chloride; The polymer contained in the second component is selected from one or more of polyacrylic acid, polymethacrylic acid, polybutenoic acid and polyvalenoic acid; Preferably, in the hygroscopic layer slurry, the molar ratio of the polymer to the inorganic metal ion compound contained in the first component is 10-50:1; Preferably, in the moisture absorption layer slurry, the molar ratio of the polymer contained in the first component to the polymer contained in the second component is 1-50:
1.
8. The preparation method according to claim 4, characterized in that: The cesium tungsten bronze nanoparticles are prepared according to the following steps: The tungsten-containing compound is dissolved in anhydrous ethanol, and then the cesium-containing compound is added to obtain a mixed solution; Acetic acid is added dropwise into the mixed solution, and cesium tungsten bronze nanoparticles are prepared by a solvothermal method.
9. The preparation method according to claim 4, characterized in that: The substrate is selected from acrylic glass, automobile glass, window glass or equipment glass.
10. A coated glass, characterized in that: The composite coating as claimed in any one of claims 1 to 3 is coated on a glass substrate.
Citation Information
Patent Citations
Preparation method of polymer coating with characteristics of self-repairing performance, water resistance, long acting, fog resistance, and frost resistance
CN105273518A
Multi-functional antifogging coating and preparation method thereof
CN106146868A
Tungsten bronze-based super-hydrophobic transparent thermal insulation coating and preparation method thereof
CN113185871A
Preparation method of heat-insulating anti-fog self-cleaning super-hydrophilic transparent coating
CN114181626A
Sunscreen cooling material with radiation refrigeration and moisture absorption volatilization effects as well as preparation method and application of sunscreen cooling material
CN116278218A
Cited By
Potassium-tungsten bronze-based photo-thermal super-hydrophobic coating as well as preparation method and application thereof
CN122381623A